(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2021)
This research aimed to study computer anxiety among students In the governorate of Darra’s schools according to the variables of achievement, sex, class, having a computer, experience, number of hours using the computer a day and economic status. This study used the descriptive analytic method. The sample was chosen randomly and the size was (656) students from Darra’s schools. Computer Anxiety Scale (CAS) was built in this study according to scientific steps which are used in the scale structure. The results showed the followings: The distribution is normal, there is a negative relationship between computer anxiety and achievement(R=-.07, α= 0,05).There is a negative relationship between computer anxiety and economic status (R=-.010, α= 0,01), sex factor hasn’t any effects on computer anxiety, class factor hasn’t any effects on computer anxiety, factor of having a computer has significant effects on computer anxiety, experience factor has significant effects on computer anxiety, the average of using the computer is (2.82) hours.